Avant-garde, internationalism, and politics Argentine art in the sixties - Giunta, Andrea (Duke University Press, 2007)
Chapter 1. Modern Art on the Margins of Peronism -- Postwar Chronicle / The North American Invasion / Abstract Artists -- Between Communists and Liberals / The Platforms for the Displaced / The Official Policy Toward Art / The French Invasion / Controversies on Abstract Art / Between Peronism and Abstract Art: Coming to Terms / Ver y Estimar on the Ramparts of Modern Art -- Chapter 2. Proclamations and Programs During the Revolución Libertadora -- The Embassies of Art / A Revitalized Museum / A New Museum for the New Art / Boa, Phases, and the International Front of the Avant-Garde / Conflicting Internationalisms / The Exploration of Materials -- Chapter 3. The "New" Art Scene -- Journal of a Collector / Coming Out in Society / The First International Exhibition / The 150th Anniversary Celebrations / A Plan for Success -- Chapter 4. The Avant-Garde as Problem -- The Material Limits / The Art of "Things" / An Aesthetic of Violence / Argentines in Paris / Avant-Garde and Narration / The Total Art Object -- Chapter 5. The Decentering of the Modernist Paradigm -- Suspending Judgment and Embracing Novelty / Other Genealogies for Modern Art / An All-Consuming Aesthetic -- Chapter 6. Strategies of Internationalization -- The American Family / International Awards for National Recognition / The Circulating MoMA Exhibitions / 1964: The Year of Recognition / Biennial and Anti-Biennial / The Culmination of Internationalism / The Aporias of Internationalism -- Chapter 7. The Avant-Garde Between Art and Politics -- The Artist as Intellectual / A "Plastic" Crime / The Politics of Assemblage / The Avant-Garde Between the Two Boundaries / Art as a Collective and Violent Action
Includes bibliographical references (p. [373]-395) and index
Keywords: Art, Argentine / 20th century; Art / Political aspects / Argentina; Avant-garde (Aesthetics) / History / 20th century / Argentina